PHÁT HIỆN VÀ PHÂN LOẠI BURKHOLDERIA SPP. TỪ MẪU ĐẤT TẠI TỈNH NGHỆ AN - Bùi, Thị Lan Anh; Ngô, Thanh Nam; Dương, Tuấn Linh; Shpak, Ivan Mikhailovic; Zakharova, Irina Borisova (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
IDENTIFICATION AND DIFFERENTIATION OF BURKHOLDERIA SPP. FROM ENVIRONMENTAL SOIL IN NGHE AN PROVINCE More than 60 species belong to Burkholderia genus were found in water and soil environment, some of them could cause diseases for both human and animals. The B. pseudomallei complex classically consisted of B. mallei, B. pseudomallei, B. thailandensis and some extended species such as B. oklahomensis, B. humptydooensis...based on similarity in phenotypes and biochemical characteristics. In this study, both realtime PCR and multiplex PCR techniques were applied to identify and classify Burkholderia spp. from environmental soil samples collected in Nghe An province. Realtime PCR method was used to classify B. mallei, B. pseudomallei while multiplex PCR method was aplied to differentiate B. pseudomallei, B. thailandensis and B. cepacia. Four Burkholderia spp. strains were isolated in which 1 strain was B. thailandensis and 3 others were B. cepacia.